2005
DOI: 10.1007/s11103-005-7876-2
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum bicolor’s Transcriptome Response to Dehydration, High Salinity and ABA

Abstract: Genome wide changes in gene expression were monitored in the drought tolerant C4 cereal Sorghum bicolor, following exposure of seedlings to high salinity (150 mM NaCl), osmotic stress (20% polyethylene glycol) or abscisic acid (125 microM ABA). A sorghum cDNA microarray providing data on 12,982 unique gene clusters was used to examine gene expression in roots and shoots at 3- and 27-h post-treatment. Expression of approximately 2200 genes, including 174 genes with currently unknown functions, of which a subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
180
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(197 citation statements)
references
References 102 publications
12
180
1
1
Order By: Relevance
“…In contrast to nonstressed conditions, when phloem loading rate and SUT expression seems to be a function of leaf sugar status (Vaughn et al, 2002, and results presented above), more complex patterns were observed under stress, probably reflecting the changes in water status and sink activity. Drought and salt stress were found to have the same effect on SUT expression in all species, which is not surprising considering the overlap of plant responses to osmotic stresses such as drought, and salinity shown in genomics studies (Kreps et al, 2002;Buchanan et al, 2005). The common pattern shows that both require the same adaptations regarding the transport of sugars.…”
Section: Sut Regulation Is Part Of the Abiotic Stress Responsesupporting
confidence: 52%
“…In contrast to nonstressed conditions, when phloem loading rate and SUT expression seems to be a function of leaf sugar status (Vaughn et al, 2002, and results presented above), more complex patterns were observed under stress, probably reflecting the changes in water status and sink activity. Drought and salt stress were found to have the same effect on SUT expression in all species, which is not surprising considering the overlap of plant responses to osmotic stresses such as drought, and salinity shown in genomics studies (Kreps et al, 2002;Buchanan et al, 2005). The common pattern shows that both require the same adaptations regarding the transport of sugars.…”
Section: Sut Regulation Is Part Of the Abiotic Stress Responsesupporting
confidence: 52%
“…Transcriptome research conducted in Arabidopsis thaliana [21,22], Oryza sativa [23,24], and Sorghum bicolor [25] has been used to successfully identify differentially expressed genes, implicating several biosynthetic pathways that assist in the overall tolerance to drought stress. Recent genomic research in quinoa has successfully identified genes (e.g., SOS1, NHX1, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…As such, sorghum offers great potential as a food source in both dry and relatively more saline regions. Several studies have been reported on the large scale screening of sorghum varieties for salt tolerance [24], transcriptome changes in response to dehydration and high salinity [25], the evaluation of growth parameters and ion accumulation [26], and soluble carbohydrate contents [27,28] among various cultivars of sorghum. Although these studies provide valuable information on the effect of salt stress on gene expression, plant growth and the accumulation of soluble sugars which may function as osmoprotectants, there is need to identify specific proteins that contribute to sorghum's salt tolerance mechanisms.…”
Section: Introductionmentioning
confidence: 99%